Agilizing the enterprise - Raynus, Joseph; Taylor and Francis (Boca Raton, FL : Auerbach Publications, an imprint of Taylor and Francis, 2018)
This book blends concepts and their application in a comprehensive and clear presentation of how mastering of visionary leadership, strategic Innovation, managed resilience, and organizational agility improve solution delivery and sustain enterprise performance. This book widens the perspective on enterprise agility and outlines an actionable strategy to assure solution alignment in support of corporate goals. The four parts of the book describe the (3z(BEnterprise Performance Enablers(3y (Bthat make enterprise agility possible. They are designed to maximize organizational effectiveness and efficiency, as well as the processes that make them happen.s
chapter 1 Meeting at the Airport / Joseph Raynus -- chapter 2 Searching for Answers in History / Joseph Raynus -- chapter 3 Searching for the Age of Agility / Joseph Raynus -- chapter 4 Searching in Change Management / Joseph Raynus -- chapter 5 Searching in Strategic Leadership / Joseph Raynus -- chapter 6 Searching for Agile Organizations / Joseph Raynus -- chapter 7 Searching for Agile Leadership Qualities / Joseph Raynus -- chapter 8 Searching for Problem Solving and Decision Making / Joseph Raynus -- chapter 9 Searching for Innovation / Joseph Raynus -- chapter 10 Moving to the Age of Agility / Joseph Raynus.
Keywords: BUSINESS & ECONOMICS / Project Management; COMPUTERS / Information Technology; Organizational change; Strategic planning